Syndecan-1 and Its Expanding List of Contacts - Stepp, Mary Ann (Adv Wound Care (New Rochelle), 2015)
Significance: The binding of cytokines and growth factors to heparan sulfate (HS) chains on proteoglycans generates gradients that control development and regulate wound healing. Syndecan-1 (sdc1) is an integral membrane HS proteoglycan. Its structure allows it to bind with cytosolic, transmembrane, and extracellular matrix (ECM) proteins. It plays important roles in mediating key events during wound healing because it regulates a number of important processes, including cell adhesion, cell migration, endocytosis, exosome formation, and fibrosis. Recent Advances: Recent studies reveal that sdc1 regulates wound healing by altering integrin activation. Differences in integrin activation lead to cell-type-specific changes in the rate of cell migration and ECM assembly. Sdc1 also regulates endocytosis and the formation and release of exosomes. Critical Issues: Understanding how sdc1 facilitates wound healing and resolution will improve treatment options for elderly and diabetic patients with delayed wound healing. Studies showing that sdc1 function is altered in cancer are relevant to those interested in controlling fibrosis and scarring. Future Directions: The key to understanding the various functions ascribed to sdc1 is resolving how it interacts with its numerous binding partners. The role played by chondroitin sulfate glycosaminoglycan (GAG) chains on the ability of sdc1 to associate with its ligands needs further investigation. At wound sites heparanase can cleave the HS GAG chains of sdc1, alter its ability to bind cytokines, and induce shedding of the ectodomain. This review will discuss how the unique structure of sdc1 allows it to play key roles in cell signaling, ECM assembly, and wound healing.